The Relationship between Notation and Performance in the Keyboard Compositions of Carl Philipp Emanuel Bach. A Composer's Specific Attempt to Communicate with Performers and Listeners - Mądry, Alina (Interdisciplinary Studies in Musicology, 2018)
.